Application of Polymerase Chain Reaction (PCR) for the Detection of Environmental Pollution (Water, Air, and Soil): A Review - Novenda, Maya; Khairunnisa, Hafidha; Hidayati, Noor Rizqi Nadzifa; Ariyani, Elza Putri (RUMPHIUS, 2024)
The environment is an important unit in the life of living creatures. The environment provides resources that are beneficial for life such as water, soil, air, minerals, flora, and fauna. Environmental pollution is a problem that often occurs and will impact the survival of living things. The aim of writing this article is to provide information on PCR technology in the living environment. Data collection was carried out by searching literature in the form of international articles for the last five years from 2018-2023 and produced 36 research articles related to PCR applications in the environment. Data searches were carried out via search engines, namely Google, PubMed, NCBI, and Publish or Perish 8 software. Based on the article, the PCR method can be used to detect microorganisms that are markers of environmental pollution.